The Role of Multimodal Prehabilitation in Improving Postoperative Functional Outcomes in Colorectal Cancer Patients: A Review - Rayhan Shafithri; Zati Hasyyati Ali; Willa Mutia Syafrida (Mitra Akademia Indonesia, 2026)
Colorectal cancer is the third most common type of cancer worldwide and the second leading cause of death. Surgery remains the primary treatment modality, but the resulting surgical stress often triggers significant metabolic, cardiovascular, and psychological responses. Post-surgery, patients are at risk of a 20% to 40% decrease in functional capacity, leading to an increased risk of complications and prolonged hospital stay. This review aims to evaluate the benefits of a multimodal pre-rehabilitation program on improving post-operative functional and clinical outcomes in colorectal cancer patients. The methods of this article were searched through Scopus and PubMed databases for the period 2021-2026. Keywords used in the literature search included